법원에서 금지한‘한국화’명칭의 사용과‘한국화’의 정체성 - 최광준(Tsche, Kwang Jun) (기초조형학연구, 2023)
본 연구의 목적은 ‘한국화’ 명칭의 사용에 관한 문제를 검토하고 이와 관련하여 근대기와 해방 이후‘한국화’의 정체성을 탐구하는 것이다. 1980년대 ‘한국화’라는 명칭을 사용하는 것에 대해 행정소송이제기됐고 법원은 ‘한국화’명칭 사용에 대한 이의를 받아들였다. 그 이후 1988년 제5차 교육과정부터는 교과서에서도 한국화라는 명칭은 사라졌고 대신 전통회화, 수묵화, 채색화라는 용어들이 사용되기시작했다. 한국에서는 많은 사람들이 ‘한국화’의 명칭을 사용하기를 꺼리고 있으며, ‘한국화’보다 일제로부터 받아들인 ‘동양화’라는 명칭을 더 많이 사용하고 있다. ‘동양화’가 ‘서양화’에 대칭되는 개념으로 한·중·일의 회화를 모두 아우를 수 있는 용어라면, 굳이 일제강점기에 일방적으로 들어 왔다는 이유만으로 그 사용에 반대할 것은 아니라고 본다. 다만, ‘동양화’를 ‘한국화’의 대체적인 명칭으로 사용하는 데에는 문제가 있다. ‘동양화’를 ‘한국화’의 대체적인 개념으로 계속 사용하다 보면, 결국은 ‘한국화’의 명칭이나 내용을 망각할 우려가 있기 때문이다. 지금 우리는 ‘동양화’의 명칭이 유입된 이후 장기간 이 포괄적인 용어에 의존해 온 나머지 오늘날 더 심하게 ‘한국화’의 정체성의 진통을 겪고 있는지도 모르겠다. 본 연구는 이러한 인식을 바탕으로 제1장의 서론을 거쳐 제2장에서 ‘한국화’의 명칭의문제를 살펴본 후, 제3장에서는 시대별로 한국화의 정체성을 고찰한다. 시대는 그 시대에 맞는 전통을만들어내고, 그 전통이 모여서 일정한 정체성을 형성한다. 본 연구를 통해 ‘한국화’는 그 시대에 맞게적응해 가면서도 뿌리를 잃지 않으며 꾸준히 발전해 왔다는 결론에 이를 수 있었다. The purpose of this study is to examine the issue of the use of the name ‘Hangukhwa(Korean Painting)’ and to explore the identity of ‘Hangukhwa(Korean Painting)’ in modern times and after liberation. In the 1980s, an administrative lawsuit was filed against the use of the name ‘Hangukhwa(Korean Painting)’ and the court upheld the objection to the use of the name. Since then, the name ‘Hangukhwa’ has disappeared from textbooks since the 5th curriculum in 1988, and the terms traditional painting, ink painting, and color painting have been used instead. In South Korea, many people are reluctant to use the term ‘Hangukhwa(Korean Painting)’ and prefer to use the term ‘Dongyanghwa(Oriental Painting)’, which was adopted from Japan. If ‘Dongyanghwa(Oriental Painting)’ is a symmetrical concept to ‘Western Painting’ and can encompass paintings from Korea, China, and Japan, it is not necessary to oppose its use just because it was unilaterally introduced during the Japanese occupation. However, there is a problem with using ‘Dongyanghwa(Oriental Painting)’ as an alternative name for ‘Hangukhwa(Korean Painting)’. If we continue to use ‘Dongyanghwa(Oriental Painting)’ as a substitute for ‘Hangukhwa(Korean Painting)’, we may eventually forget the name and content of ‘Hangukhwa(Korean Painting)’. It may be that we are experiencing a more severe identity crisis of ‘Hangukhwa(Korean Painting)’ today because we have relied on this umbrella term for so long. Based on this recognition, this study, after an introduction in Chapter 1, examines the issue of the name ‘Hangukhwa’ in Chapter 2, and then examines the identity of ‘Hangukhwa(Korean Painting)’ by period in Chapter 3. Each era creates its own traditions, and those traditions come together to form a certain identity. As a result of examining the development of ‘Hangukhwa(Korean Painting)’, it can be concluded that ‘Hangukhwa(Korean Painting)’ has developed steadily without losing its roots while adapting to the times. KCI Citation Count: 0